The taxonomy of Moroccan fir Abies marocana (Pinaceae): conceptual clarifications from phylogenetic studies - Ben-Said, Mariem (Mediterranean Botany, 2022)
Western Mediterranean firs are endemic and illustrate the Tertiary flora heritage in the Mediterranean basin. Due to their morphological and anatomical similarities, the classification of certain relict firs still debated especially those belonging to the Piceaster section. Moroccan fir Abies marocana is one of these taxa whose taxonomy has remained unresolved for a long time. Many authors recognized two species in the Rif Mountains A. marocana and A. tazaotana while others considered these taxa as varieties or subspecies of A. pinsapo. Recently, several biometrical and molecular studies contributed to a better understanding of their phyletic relationships. In this review, the main findings of recent studies are synthetized with the aim of shedding light on the evolution of the taxonomical position of Moroccan relict fir. The main hypotheses explaining the phylogenetic relationships between Moroccan and Spanish firs are also discussed. The results converged towards the separation of Moroccan and Spanish firs at the species level, while they did not support the distinction between A. marocana and A. tazaotana as different species.